Rancang Bangun E-Learning Rembulan Menggunakan Moodle sebagai LMS pada SMK Negeri 1 Pandeglang - Dheo Dermawan; Muhamad Fachri Lutfian; Bagus Maulana Muhammad (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
This research presents the development of the Rembulan E Learning platform using Moodle as the primary Learning Management System for SMK Negeri 1 Pandeglang.The main objective is to provide a structured, accessible, and interactive digital learning environment that effectively supports teaching and learning activities, enhances student engagement, and facilitates teacher management of course materials. The study applies the Waterfall development model, which includes five stages requirement analysis, system design, implementation, testing, and deployment. Data collection methods involve observation of classroom practices, in depth interviews with teachers to identify pedagogical and technological needs, and comprehensive documentation review to ensure alignment with curriculum standards and user expectations. The resulting system integrates features such as digital classrooms, learning modules, assignments, discussion forums, quizzes, and student performance monitoring, offering a comprehensive digital learning experience. System testing was conducted using Black‑box Testing, complemented by limited user trials with teachers and students, which confirmed that the platform is functional, user friendly, and capable of supporting a variety of learning activities. This research contributes to the implementation of Moodle based LMS development in vocational schools, providing practical guidance for improving digital learning quality, promoting blended learning approaches, and facilitating sustainable adoption of educational technology in secondary education.